Determinant factors that influence customers’ experience in fast food restaurants in Sungai Petani, Kedah - Azila Jaini; Nor Asma Ahmad; Siti Zamanira Mat Zaib (2015)
This study investigates the relationship between total restaurant quality and customers’ experience in a local fast food restaurant. The objectives of this study are to determine the factors that lead to customers’ positive experience and to recognize the elements that encourage people to dine-in at a chosen fast food restaurant. The study was conducted quantitatively, in which the convenience sampling method was chosen to collect the data. 373 questionnaires were collected and the findings were analyzed using the Predictive Analytics Software (PASW). Four critical factors of total restaurant quality were tested and the findings of this study proved that there is a positive relationship between three factors (food quality, service quality, and perceived value) and customers’ experience. Perceived value is the main reason for people to dine-in at a chosen fast food restaurant. Overall, this study suggests that a fast food restaurant should focus on delivering services to the customers and simultaneously enhancing the other qualities in order to capture long-term relations with customers.